Poverty and Inequality in contemporary Portugal: impact of the austerity policies and lessons for the future - Monteiro, Alcides (Sociološki pregled, 2020)
In the European Union, Portugal is one of the countries with the highest levels of poverty and inequality. This is the reality that this article focuses on. The text provides statistical data that illustrate the evolution of poverty and income inequalities over the last decade (2011-2019), serving as a basis for a critical analysis of the consequences of economic cycles on it. In particular, how the combination of the economy (financial crisis), politics (austerity plan) and social context (low social contestation) has interfered with its worsening over the period 2011-2014. From this analysis, we develop the argument that if the negative alliance of the three factors makes a country poorer and more unequal, it is in turn the positive combination of the same factors that could lead to important advances in the fight against poverty and social inequality.